2023
DOI: 10.1089/thy.2022.0504
|View full text |Cite
|
Sign up to set email alerts
|

Surgery After BRAF-Directed Therapy Is Associated with Improved Survival in BRAFV600E Mutant Anaplastic Thyroid Cancer: A Single-Center Retrospective Cohort Study

Abstract: Background: The aim of this study was to describe the oncologic outcomes of patients with BRAF V600E -mutated anaplastic thyroid cancer (ATC) who had neoadjuvant BRAF-directed therapy with subsequent surgery. For context, we also reviewed patients who received BRAF-directed therapy after surgery, and those who did not have surgery after BRAF-directed therapy. Methods: This was a single-center retrospective cohort study conducted at a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 22 publications
(27 reference statements)
0
34
0
Order By: Relevance
“…Zhao et al [17 ▪ ] recently published a retrospective cohort study of 32 patients with BRAFm-ATC treated with neoadjuvant BRAF-directed therapy followed by surgery, where this treatment approach allowed significant reduction in tumor size, extent of surgery, and surgical morbidity. Notably, eight of nine patients who had unresectable disease at initial presentation were recategorized as having only moderate or mild surgical morbidity.…”
Section: Updates In the Management Of Anaplastic Thyroid Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al [17 ▪ ] recently published a retrospective cohort study of 32 patients with BRAFm-ATC treated with neoadjuvant BRAF-directed therapy followed by surgery, where this treatment approach allowed significant reduction in tumor size, extent of surgery, and surgical morbidity. Notably, eight of nine patients who had unresectable disease at initial presentation were recategorized as having only moderate or mild surgical morbidity.…”
Section: Updates In the Management Of Anaplastic Thyroid Carcinomamentioning
confidence: 99%
“…For instance, the ROAR trial excluded patients with an Eastern Cooperative Oncology Group performance status > 2, and those unable to swallow the trial medication. In the past year, multiple real-world studies have been published confirming the efficacy and safety of DT outside the setting of a clinical trial [12 ▪▪ ,17 ▪ ,21 ▪ –23 ▪ ], although they reported shorter OS and PFS durations compared to the phase II trial. These differences are likely due to greater patient heterogeneity and potential delays in access to drugs.…”
Section: Updates In the Management Of Anaplastic Thyroid Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies met criteria for inclusion in the final review. 5,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, six further studies were subsequently excluded due to overlapping patient data 5,12,28,[32][33][34] leaving 15 studies to be included in the final review [16][17][18][19][20][21][22][23][24][25][26][27][29][30][31] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Eight out of the 15 included studies (53.3%) provided details pertaining to postoperative surgical morbidity 16,17,20,21,24,[29][30][31] (Table 4). or restricted radical surgery (14.3%).…”
Section: Postoperative Morbiditymentioning
confidence: 99%

Thyroid Cancer

Boucai,
Zafereo,
Cabanillas
2024
JAMA
Self Cite